LEARNING OUTSIDE THE CLASSROOM: WHAT STREET CULTURE, TRAVEL, AND LIFE EXPERIENCE TEACH US (British Journal of Global Ecology and Sustainable Development, 2025)
This article analyzes the role and importance of extracurricular education in teaching English. Extracurricular activities allow students to apply the acquired theoretical knowledge in practice, communicate in real-life situations, develop independent thinking and cultural thinking. Through English clubs, theater stages, conversations, trips, and cultural events, students learn the language in a natural environment. The article also highlights the importance of extracurricular education in increasing students' motivation, strengthening confidence in communication, and connecting language learning with life.